The Determinants of Consumptive Behaviour of Social Studies Students in State Senior High School Salatiga (Universitas Negeri Semarang, 2022)
The development of technology is increasingly changing the order of people's lives in various activities in an effort to meet every need. The use of technology is expected to facilitate the activities of human life to be practical, effective and efficient. This situation encourages Social Studies Students in State Senior High School Salatiga to spend all their pocket money through online shopping applications and payments in excess and not based on need. The purpose of the study was to analyze the effect of using electronic money, performance expectancy, self concept, and economic literacy on consumptive behavior through lifestyle. Data collection used instruments in the form of questionnaires and tests. Data analysis was done by descriptive analysis of research variables, path analysis, and Sobel test. The population in this study was the social studies students of the State Senior High School of Salatiga, which amounted to 1,133 students with a sample of 296 students. The results of data analysis show, 1) there is no effect of using electronic money on lifestyle. 2) performance expectancy has a positive effect on lifestyle. 3) self concept has a positive effect on lifestyle. 4) economic literacy has a positive effect on lifestyle. 5) the use of electronic money has no effect on consumptive behavior through lifestyle. 6) performance expectancy effect on consumptive behavior through lifestyle. 7) self concept effect on consumptive behavior through lifestyle. 8) economic literacy effect on consumptive behavior through lifestyle. 9) lifestyle has a positive effect on consumptive behavior.